On the moments of the moments of ζ(1/2 + it) - Bailey, EC; Keating, J (Elsevier, 2021)
Taking t at random, uniformly from [0,𝑇], we consider the kth moment, with respect to t, of the random variable corresponding to the 2βth moment of ζ(1/2+𝒾x) over the interval x ∈ (𝑡,𝑡+1), where ζ(s) is the Riemann zeta function. We call these the ‘moments of moments’ of the Riemann zeta function, and present a conjecture for their asymptotics, when 𝑇 → ∞, for integer 𝑘, 𝛽. This is motivated by comparisons with results for the moments of moments of the characteristic polynomials of random unitary matrices and is shown to follow from a conjecture for the shifted moments of ζ(𝒮) due to Conrey, Farmer, Keating, Rubinstein, and Snaith [18]. Specifically, we prove that a function which, the shifted-moment conjecture of [18] implies, is a close approximation to the moments of moments of the zeta function does satisfy the asymptotic formula that we conjecture. We motivate as well similar conjectures for the moments of moments for other families of primitive L-functions.